2006
DOI: 10.1123/ijsnem.16.6.580
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Exercise Program and a Calcium Supplementation on Bone in Children: A Randomized Control Trial

Abstract: We investigated the effects of calcium supplementation and physical practice on the bone ultrasound properties and trabecular microarchitecture in children. 160 children aged 8-11 were randomly allocated to active or nonactive groups and to receive either a calcium-phosphate or a placebo powder for 6 months. Skeletal status was assessed using an ultrasound technique, which measures the speed of sound (Ad-SoS, m/s) at the phalanx. Bone microarchitecture was characterized by fractal analysis measured on calcaneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…BMA feasibility in children To our knowledge, there are few published data of BMA in children [20]. The standard site to perform BMA is the calcaneus, and one technical limitation could be results' variability after repositioning.…”
Section: Discussionmentioning
confidence: 96%
“…BMA feasibility in children To our knowledge, there are few published data of BMA in children [20]. The standard site to perform BMA is the calcaneus, and one technical limitation could be results' variability after repositioning.…”
Section: Discussionmentioning
confidence: 96%
“…In a later publication, the authors stated: "Based on these observations, bone appears to be most responsive to mechanical stress during Tanner stages II through IV, corresponding to the two year window that has been identified for peak bone mineral accrual around the time of puberty." (9) In fact, a large number of studies have reported an osteogenic response to exercise in early pubertal children (34,42,55,56,60,61,63,66); in some cases in the absence of effect in pre-pubertal children in the same trial (56,72). A 1997 ten-month study of 71 'pre-menarcheal' girls, who appeared to be Tanner Stages I and II, reported improvements in overall bone outcomes but no maturation-based comparisons were made (66).…”
Section: Evidence For An Optimal Effect Of Exercise On Bone During Pumentioning
confidence: 99%
“…A significant, positive effect of calcium supplementation on bone mineral density has been demonstrated in pre-and peripubertal children [5,[8][9][10][11][12][13][14]. Milk products with the addition of protein and phosphorus are also associated with bone density gains in this age group [15].…”
Section: Introductionmentioning
confidence: 99%